2018
DOI: 10.3389/fphys.2018.00175
|View full text |Cite
|
Sign up to set email alerts
|

Naltrexone Reverses Ethanol Preference and Protein Kinase C Activation in Drosophila melanogaster

Abstract: Alcohol use disorder (AUD) is a major health, social and economic problem for which there are few effective treatments. The opiate antagonist naltrexone is currently prescribed clinically with mixed success. We have used naltrexone in an established behavioral assay (CAFE) in Drosophila melanogaster that measures the flies' preference for ethanol-containing food. We have confirmed that Drosophila exposed to ethanol develop a preference toward this drug and we demonstrate that naltrexone, in a dose dependant ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Interspecies transcriptomic and proteomic analyses combined with behavioral mutant analyses will help to narrow the list of crucial regulators of AUDs. In the future, Drosophila and C. elegans can be used as screening platforms to test the efficacy of pharmacological compounds to disrupt alcohol‐related behaviors (Koyyada et al., ; Ranson et al., ; Scott et al., ,b). Finally, the use of Drosophila and C. elegans as genetic model organisms can also be extended to study other drugs of abuse, such as nicotine or cocaine (reviewed by Dupuis et al., ; Engleman et al., ; Haydon et al., ; Kaun et al., ; Kudelska et al., ; Lowenstein and Velazquez‐Ulloa, ; Matta et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interspecies transcriptomic and proteomic analyses combined with behavioral mutant analyses will help to narrow the list of crucial regulators of AUDs. In the future, Drosophila and C. elegans can be used as screening platforms to test the efficacy of pharmacological compounds to disrupt alcohol‐related behaviors (Koyyada et al., ; Ranson et al., ; Scott et al., ,b). Finally, the use of Drosophila and C. elegans as genetic model organisms can also be extended to study other drugs of abuse, such as nicotine or cocaine (reviewed by Dupuis et al., ; Engleman et al., ; Haydon et al., ; Kaun et al., ; Kudelska et al., ; Lowenstein and Velazquez‐Ulloa, ; Matta et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…When flies are nonvoluntarily exposed to EtOH, they develop EtOH consumption preferences that are long‐lasting and independent of the EtOH's caloric value (Peru et al., ). The preference to consume EtOH‐enriched food can be reduced by feeding with naltrexone (Koyyada et al., ). In the Drosophila brain, cAMP signaling regulates EtOH consumption preference in the mushroom bodies, a brain structure required for appetitive olfactory learning and memory, using sugar as reward (Xu et al., ).…”
Section: Decision Making Reward and Learning: Dissecting Relationshmentioning
confidence: 99%
“…In this work, Drosophila was confirmed to be a useful model for studying alcohol-induced behaviours as has been amply demonstrated in other studies (Kaun et al, 2012; Robinson et al, 2013). Previous Drosophila work had identified a number of GPCRs that are involved in the response to alcohol, including the dopamine/ecdysteroid receptor (Petruccelli et al, 2016), neuropeptide F receptor (Wen et al, 2005), putative opioid receptors (Koyyada et al, 2018) and GABA B receptor (Ranson et al, 2019). An earlier extensive review of mammalian studies of the effect of psychostimulants on G-protein expression (Kitanaka et al, 2008) highlighted that only limited work had been focused on ethanol-induced changes in any animal models, with only one study reporting a reduction in G-protein b1 in rat hippocampus (Saito et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Tests of similar learning and memory genes revealed additional notable alcohol phenotypes caused by manipulations of rutabaga (rut) [11,142,197,198], encoding fly adenylyl cyclase, and dnc [193,199,200]. Separate from these pathways and studies, other studies have suggested alcohol-related roles of other genes in the network, including the cAMP-dependent protein kinase A (PKA) [114,197,201], protein kinase C (PKC) [79,[202][203][204], CREB [205][206][207], and CREB binding protein (CBP) [117,208], consistently suggesting a causal role of cAMP signaling pathways in alcohol abuse. The K + channel KCNQ is another example of the one-gene-at-a-time approach and the phenomenon of fly and human studies autonomously arriving at corroborating conclusions.…”
Section: Behavioral Screens In Drosophilamentioning
confidence: 99%